Determination of the peculiarities of obtaining coatings of different hardness on structural steel at diffusion metalization - Markov, Oleg; Diachenko, Yurii; Aliieva, Leila; Zharikov, Serhii; Hrudkina, Natalia; Bondarenko, Volodymyr; Pohorielov, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2019)
The features of obtaining coatings on carbon steel, structural steel St 3 are studied during diffusion metallization – simultaneous saturation of steel with boron, chromium and aluminum (boron chromium aluminizing), without the use of special heat treatment. The basic compositions of powder mixtures are established using the simplex lattice method, which make it possible to obtain boride structures of increased hardness, phases of a solid solution of boron, chromium and aluminum in Feα and the predicted depth of the surface layer on the surface of carbon steel. The characteristic features of the microhardness formation of the surface layer of coatings are established depending on the composition of the saturating mixture. An important factor is established for the effect of aluminum on the microhardness of the surface layer in multicomponent systems. Its presence contributes to the formation of solid solutions. New data are obtained on the formation of surface layers during steel saturation with boron, chromium and aluminum, and the conditions for obtaining layers of high hardness and high ductility are determined. The optimal areas for the formation of coatings of various structures and depths by the simplex planning method are found. As optimization factors, let’s use the relative planes occupied by borides and solid solution, as well as the depth of the surface layers. It is clearly shown how the structure of surface layers changes depending on the quantitative relations between the components of saturating mixtures. The graphical dependences of the boride phase, the phase of the solid solution and the depth of the layer, on the composition of the saturating mixture during diffusion metallization (boron chromium aluminizing) allow to improve the process in order to obtain coatings with increased wear resistance on the surface of carbon steel